OP02 Bridging the Gap: Reducing Delays in Axial Spondyloarthritis Diagnosis through Innovative Public Health Campaigning - Eddison, Joe; Kennedy, N; Heron, N; Pendleton, Adrian; Webb, Dale (Rheumatology (Oxford, England), 2024)
Background and aims The Act on Axial SpA campaign is dedicated to minimising the lengthy 8.5-year delay in diagnosing axial spondyloarthritis (axial SpA) by implementing a pioneering Gold Standard diagnosis time of just one year. Collaborating with the Belfast Health & Social Care Trust, our initiative aims to streamline the patient journey from symptom onset to diagnosis through a comprehensive, integrated intervention package. By enhancing awareness of Axial SpA and optimising diagnostic procedures alongside specialist care pathways, our pilot project endeavours to abbreviate the time to diagnosis, thereby serving as a blueprint for broader implementation across healthcare systems. Methods In partnership with a specialist Belfast-based creative agency, we devised a geo-targeted, multi-channel media campaign to bolster public awareness. Our strategy encompassed out-of-home advertising, radio promotions, and targeted social media adverts. The campaign featured 85 out-of-home advertising panels across 85 locations, radio slots on Cool FM, and geographically tailored social media adverts on Facebook and Instagram. Spanning six weeks during January and February 2024, we meticulously tracked the campaign's performance through standard social media and digital analytics platforms. Results Our campaign resonated strongly with individuals experiencing low back pain, prompting them to take action by utilising the NASS symptom checker. Over the six-week period, our social media outreach amassed an impressive 995,399 impressions and reached 831,390 individuals. Out-of-home advertising achieved an 81% reach among 18–40-year-olds in Belfast, engaging over 88,000 individuals. Additionally, radio partnership adverts reached more than 565,000 adults across Northern Ireland. This extensive reach translated into robust engagement metrics: • Social media ads garnered 16,799 clicks and 227,158 engagements. • Radio advertising led to 2,390 readership engagements on Cool FM. • The Act on Axial SpA website witnessed a surge in traffic, with 2,976 users from Belfast visiting during the campaign, compared to 285 in the entirety of 2023. • Remarkably, the NASS symptom checker experienced a staggering 4,389% increase in average daily completions during the campaign. (Figure 1) OP02 Figure 1.Number of people completing the NASS symptom checker in Belfast. (Source: Google Analytics). Conclusions Our findings demonstrate the efficacy of engaging individuals with longstanding low back pain through innovative, visually compelling marketing materials infused with public health messaging. Moreover, early clinical data suggests that heightened public awareness can be achieved without overwhelming the healthcare system, while expediting patients' journeys towards diagnosis. By continuing to monitor referrals and diagnoses, we aim to assess the long-term impact of our campaign on addressing delays in axial SpA diagnosis.